2002
DOI: 10.1097/00006416-200207000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Anterior Cruciate Ligament Injury

Abstract: Pathology, part of the basic science of medicine and nursing, is an understanding of how cellular mechanisms and organ systems function conjointly in the physical body. An awareness of the biomechanics and pathophysiology related to a particular mechanism of injury (MOI) provides a more appreciative sense of how tissues become damaged. Cognizance of the variables and risk factors involved in MOI specific to anatomic structures not only helps the Health Care Provider (HCP) decide which treatment options are nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…It is reported that more than 200,000 ACL ruptures occur every year in the United States (Childs, 2002), predominately affecting individuals aged between 15 and 44 (Smith et al, 1993). Based on animal models, it is known that transection of the ACL increases the risk for initiation of cartilage breakdown and leads to a degeneration of the structures surrounding the knee joint (Herzog et al, 1993;Brandt et al, 1991;Galois et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that more than 200,000 ACL ruptures occur every year in the United States (Childs, 2002), predominately affecting individuals aged between 15 and 44 (Smith et al, 1993). Based on animal models, it is known that transection of the ACL increases the risk for initiation of cartilage breakdown and leads to a degeneration of the structures surrounding the knee joint (Herzog et al, 1993;Brandt et al, 1991;Galois et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, about 8 patients per 10,000 people aged 15 to 44 experienced an ACL injury [5]. In United States, 250,000 patients with ACL injury were diagnosed for a year [3]. ACL injury can cause joint instability and functional instability can be induced by aberrant neuromuscular regulation due to reduced proprioceptive sensation in patients with an ACL injury.…”
Section: Introductionmentioning
confidence: 99%
“…Injury to the ACL can occur secondary to excessive valgus stress, forced external rotation of the femur on a fixed tibia, andhyperextension. [6][7][8] . the most important finding of the present study is that there were bony morphological differences between ACL-insufficiency patients and ACLintact subjects.…”
Section: Discussionmentioning
confidence: 99%